Editorial (diségno, 2024)
For a journal that deals with architectural drawing and representation, the topic of this issue No. 14, Analog Models, edited by Alberto Sdegno and Pedro Manuel Cabezos-Bernal, is certainly of great appeal, and this is demonstrated by the high number of contributions arrived at the editorial office at the end of the call for papers. [read more]